PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN DENGAN MEDIA STORYBOOK DIGITAL PADA PEMBELAJARAN BAHASA INDONESA BAGI SISWA DENGAN RESIKO SLOW LEARNER KELAS IV - Wahyudi; Indriyana Rachmawati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Reading skills are fundamental competencies that remain challenging for students at risk of being slow learners, as they often experience difficulties in word recognition, reading fluency, and reading comprehension. These conditions require instructional media that are engaging and responsive to students' learning characteristics. This study aimed to improve the reading skills of students at risk of being slow learners through the implementation of digital storybook media in Grade IV at SD Negeri 002 Muara Ancalong. The study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles. The participants were Grade IV students identified as being at risk of becoming slow learners. Data were collected through observations, reading skill tests, interviews, and documentation, and analyzed using descriptive quantitative and qualitative techniques. The findings showed that students' average reading achievement increased from 52.98% in the initial condition to 66.07% in Cycle I and 94.05% in Cycle II, indicating that the predetermined success criteria were achieved. Improvements were observed in reading fluency, pronunciation accuracy, reading comprehension, and students' participation during classroom activities. The novelty of this study lies in the use of digital storybook media as an interactive learning resource specifically designed to accommodate the learning characteristics of students at risk of being slow learners by integrating text, illustrations, and digital features that encourage active reading engagement. These findings indicate that digital storybook media can serve as an alternative instructional medium to support the improvement of reading skills among elementary school students at risk of being slow learners. ABSTRAK Kemampuan membaca merupakan keterampilan dasar yang masih menjadi tantangan bagi siswa dengan risiko slow learner karena mereka cenderung mengalami kesulitan dalam mengenali kata, membaca secara lancar, dan memahami isi bacaan. Kondisi tersebut memerlukan penggunaan media pembelajaran yang menarik dan sesuai dengan karakteristik belajar siswa. Penelitian ini bertujuan untuk meningkatkan kemampuan membaca siswa dengan risiko slow learner melalui penerapan media storybook digital di kelas IV SD Negeri 002 Muara Ancalong. Penelitian menggunakan pendekatan Penelitian Tindakan Kelas (PTK) model Kemmis dan McTaggart yang dilaksanakan dalam dua siklus. Subjek penelitian adalah siswa kelas IV yang teridentifikasi memiliki risiko slow learner. Data dikumpulkan melalui observasi, tes kemampuan membaca, wawancara, dan dokumentasi, kemudian dianalisis secara deskriptif kuantitatif dan kualitatif. Hasil penelitian menunjukkan adanya peningkatan kemampuan membaca siswa dari rata-rata 52,98% pada kondisi awal menjadi 66,07% pada Siklus I dan meningkat menjadi 94,05% pada Siklus II, sehingga indikator keberhasilan penelitian tercapai. Peningkatan terjadi pada aspek kelancaran membaca, ketepatan pengucapan, pemahaman isi bacaan, serta partisipasi siswa selama pembelajaran. Kebaruan penelitian ini terletak pada pemanfaatan media storybook digital sebagai media interaktif yang dirancang untuk mengakomodasi karakteristik belajar siswa dengan risiko slow learner melalui penyajian teks, ilustrasi, dan fitur digital yang mendukung keterlibatan siswa dalam proses membaca. Temuan penelitian menunjukkan bahwa penerapan storybook digital dapat menjadi salah satu alternatif media pembelajaran untuk memperbaiki kemampuan membaca siswa dengan risiko slow learner di sekolah dasar.